"Such" or "Other"? Options in 1 Corinthians 11.16. Issue 3 (December 2020) - Clark, David J.
This note summarises the different ways numerous translations have rendered the Greek word toiautēn in 1 Cor 11.16, the implications that the different options could have for interpreting the verse, and how readers in various cultures may perceive Paul's attitude towards his original readers.